2022
DOI: 10.1093/treephys/tpac100
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of the FERONIA receptor kinase MdMRLK2 confers apple drought tolerance by regulating energy metabolism and free amino acids production

Abstract: Drought is a major abiotic stress limiting the growth and production of apple trees worldwide. The receptor-like kinase FERONIA is involved in plant growth, development, and stress responses, however, the function of FERONIA in apple under drought stress remains unclear. Here, the FERONIA receptor kinase gene MdMRLK2 from apple (Malus domestica) was shown to encode a plasma membrane-localized transmembrane protein and was significantly induced by abscisic acid and drought treatments. 35S::MdMRLK2 apple plants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…To protect apple from freezing damage, it is important to understand better the mechanisms by which it responds to cold stress. In previous studies, we showed that MdMRLK2 ‐OE enhanced apple drought resistance (Jing et al., 2023) but compromised Valsa canker resistance (Jing et al., 2022). In this study, we discovered that MdMRLK2 ‐OE also positively affects apple cold tolerance.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…To protect apple from freezing damage, it is important to understand better the mechanisms by which it responds to cold stress. In previous studies, we showed that MdMRLK2 ‐OE enhanced apple drought resistance (Jing et al., 2023) but compromised Valsa canker resistance (Jing et al., 2022). In this study, we discovered that MdMRLK2 ‐OE also positively affects apple cold tolerance.…”
Section: Discussionmentioning
confidence: 84%
“…Leaves were placed in dark conditions for 20 min, and a FluorCam FC800 system (Photon Systems Instruments) was used to photograph the chlorophyll fluorescence (Jing et al., 2023). The minimum fluorescence ( F 0 ), maximum fluorescence ( F m ), maximum photochemical efficiency of PSII photochemistry ( F v /F m ), actual photosynthetic efficiency of PSII Y ( II ), quantum yield of non‐regulated energy dissipation Y ( NO ), and quantum yield of regulated energy dissipation Y ( NPQ ) were measured using a Dual‐PAM‐100 chlorophyll fluorometer.…”
Section: Methodsmentioning
confidence: 99%
“…was found to be located within LOC_Os03g03290 gene model which encodes Receptor-like protein kinase FERONIA-like. The receptor-like kinase FERONIA was previously found to be tightly involved in plant development, plant growth, responses to various stresses (Jing et al 2023 ). In apple plants, the FERONIA receptor kinase was associated with induced abscisic acid under different drought treatments.…”
Section: Discussionmentioning
confidence: 99%
“…In apple plants, the FERONIA receptor kinase was associated with induced abscisic acid under different drought treatments. The activity of receptor-like protein kinase FERONIA-like was associated with less photosystem damage and higher photosynthetic rates under drought conditions (Jing et al 2023 ). Also, Receptor-like kinase OsSIK1 was found to significantly improve drought and salt stress tolerance in rice through the activation of the antioxidative system (Ouyang et al 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the Arabidopsis mutant feronia ( fer ), the pollen tube fails to arrest and thus continues to grow inside the female gametophyte without rupture for the release of sperms [ 17 , 18 ]. Besides the role in reproduction, accumulating evidence suggests that FER plays critical roles in a diversity of biological processes, such as root growth [ 135 , 136 , 137 ], immune responses [ 21 , 138 , 139 , 140 , 141 , 142 ], environmental adaptations [ 143 , 144 , 145 , 146 ], etc.…”
Section: Cwi Signal Candidates In Fruit Ripeningmentioning
confidence: 99%